Single-solution simulated Kalman Filter algorithm for routing in printed circuit board drilling process - Nor Hidayati, Abdul Aziz; Zuwairie, Ibrahim; Nor Azlina, Ab. Aziz; Zulkifli, Md. Yusof; Mohd Saberi, Mohamad (Springer Singapore, 2018)
Optimal drilling path for printed circuit board is crucial in increasing productivity and reduce production costs. Single-solution Simulated Kalman Filter (ssSKF) is a new optimizer inspired by the Kalman filtering process. It uses only a single agent to solve optimization process by finding the estimate of the optimal solution. Principally, ssSKF algorithm uses the standard Kalman filter framework, aided by a local neighborhood technique during its prediction step. This paper reveals the potential of ssSKF as a good routing method in printed circuit board (PCB) drilling process. Experimental results indicate that the ssSKF algorithm outperforms the existing methods in searching a good route to speed up a PCB drilling process.